Pendeteksi Kebocoran Gas dan Kebakaran Dini Menggunakan NodeMCU Berbasis Telegram - Raditya, Cokorda Gde Indra; Dharma, Putu Adhitya Santika; Putra, I Kadek Ardian Ananda; Sugirianta, Ida Bagus Ketut; Purnama, Ida Bagus Irawan (Jurnal Teknologi Elektro; Vol 21 No 1 (2022): ( Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2022)
The utilization of natural resources and energy is increasing day by day, one of which is the use of natural gas as fuel for both household and industrial needs. Safety aspects in the use of this gas must be considered because gas leaks can trigger fires. Therefore we need a tool that can detect and notify gas leaks as early as possible. This study proposes a gas leak detector based on the Internet of Things (IoT) using NodeMCU ESP8266 as a microcontroller. This detection system uses the MQ-2 sensor as a detector of gas levels and a flame sensor as a detector of ultraviolet light as an indication of a fire. The resulting output is a notification message from the Telegram Bot sent via NodeMCU. In this case, the buzzer and LED will give a signal if the MQ-2 sensor detects gas levels above 500 ADC, then the NodeMCU will send a command to the Telegram Bot to send a notification message in real-time. In addition, the detected gas levels are also displayed on the 16x2 LCD screen. The experimental results show that the ideal distance to detect gas is under 6 cm and fire below 20 cm with a sensor response time of 2 seconds. The existence of this tool is expected to minimize the risk of fire due to gas leakage. Keywords—fire, gas leak, NodeMCU, Telegram